Answer:
y+1=7/13(x-6)
Step-by-step explanation:
the equation for point-slope form is y-y1=m(x-x1), where (x1,y1) is a point and m is the slope
first, we'll find the slope (m)
from two points, the slope is calculated as (y2-y1)/(x2-x1)
we're given (6,-1) and (-7,-8)
we can label the points
x1=6
y1=-1
x2=-7
y2=-8
now substitute into the formula
m=(-8--1)/(-7-6)
m=-7/-13
m=7/13
the slope (m) is 7/13
we already have labeled values for (x1,y1) which we made (6,-1)
substitute our known values into the equation
y--1=7/13(x-6)
simplify
y+1=7/13(x-6)
hope this helps!